Unraveling hegemony digital: A framework CDA-semiotic framework for sustainable social epistemic justice - Anam, Mohamad Nurul (Journal of Socio-Cultural Sustainability and Resilience, 2025)
Background: In an increasingly digitized world, religion and culture have transcended their traditional roles. They are now instruments of hegemony that shape—and often destroy—our collective perception of social sustainability. This research examines how digital media platforms, through algorithms and "echo chambers", perpetuate such "organized ignorance", a systemic erosion of critical thinking caused by structural pressures and ideological manipulation. This research is rooted in the philosophical principle of Enlightenment (Kant: "Sapere Aude") and the critique of epistemic passivity (Bonhoeffer, Nietzsche). The core argument is that digital ecosystems paradoxically democratize knowledge while simultaneously reinforcing cognitive conformity and threatening socio-cultural resilience. Method: Using a qualitative design, this study applies Teun van Dijk's Critical Discourse Analysis (CDA) and Saussurean semiotics to deconstruct power-laden narratives in religious-cultural content on platforms such as YouTube. Primary data are taken from one of Ardhianzy’s videos on collective ignorance, and secondary metadata illustrate how algorithms reduce complex symbols (e.g., Kantian Enlightenment, Luther’s Reformation) into binary myths. This process legitimizes polarization and perpetuates epistemic injustice. Findings: The findings confirm the symbiotic role of algorithmic personalization and capitalist platforms in commercializing Enlightenment rhetoric. This fuels banality malorum (Arendt) through the normalization of misinformation and affective polarization. The research also identifies historical hegemonic mechanisms—such as colonial "enlightenment" missions and Nazi propaganda—that resurface in the digital context. This is reflected in Indonesia’s socio-political fragmentation, manifested through coordinated disinformation campaigns. Conclusion: This research recommends the integration of "algorithmic literacy" into SDG-based education, enhanced regulatory transparency (e.g., the EU Digital Services Act), and the development of virtue ethics-based platforms to restore intellectual autonomy. By synthesizing CDA, semiotics, and moral philosophy, the study maps hidden power structures in digital narratives and proposes actionable strategies. Novelty/Originality of this Article: This methodological synthesis of CDA, semiotics, and moral philosophy represents a novelty not present in previous unidisciplinary studies. Theoretically, this research bridges Kantian Enlightenment with contemporary critiques of digital hegemony.